Equilibrium Stability of Asymmetric Evolutionary Games of Multi-Agent Systems With Multiple Groups in Open Electricity Market - Linfei Yin; Shengyuan Li; Fang Gao (IEEE Access, 2020)
The asymptotically stable equilibrium points of asymmetric evolutionary games for multiple groups with multiple game strategies are obtained. The evolution of four groups and more multiple groups in open electricity market are described by the replicator dynamics. Multiple game strategies of the power generation enterprises in open electricity market are studied. Besides, the corresponding asymptotic stability conditions are given by the Lyapunov stability criterion.